Prostate-Specific Antigen Levels of Prostate Cancer Patients Three Months Following LHRH Agonist Therapy (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: LHRH agonist; prostate cancer; prostate-specific antigen; drug efficacy